EFFECTIVENESS OF MANUAL THERAPY AND MYOFASCIAL TRIGGER POINT THERAPY IN MANAGEMENT OF UPPERTRAPEZIUS MYOFASCIAL TRIGGER POINTS - Mukhtar, Zarmina; Jan, Mohammad Bin Afsar; Khan, Danish Ali; Rahman, Mujeeb Ur (Annals of Allied Health Sciences, 2015)
AIM: To determine the effectiveness of manual therapy and myofascial trigger point therapy in management of upper trapezius myofascial trigger points. METHOD: This study was a single blinded randomized control trial conducted at outpatient service department of physiotherapy, Khyber Teaching Hospital, Peshawar. Total of 30 patients with upper trapezius myofascial trigger points (MTrPs), aged between 20-60 years were selected by consecutive sampling technique. Patients who fulfilled the inclusion criteria were randomly assigned into two groups having 15 patients each with equal male to female ratio. One group received manual therapy at C3-C4 level. Other group received MTrPs therapy. Total 6 treatment sessions, 3 sessions per week for 2 weeks duration with one week follow up were given on a schedule starting from Monday, Wednesday and Friday or from Tuesday, Thursday and Saturday. A home exercise program composed of upper trapezius stretch, deep cervical strengthening and scapular stabilization exercises were also prescribed to the patients in both groups for 3 weeks duration starting from first treatment session till last follow up session.Visual analogue scale (VAS) and neck disability index (NDI) were used as standards for assessment of pain and disability. Initial data was taken at start of the treatment prior to the treatment sessions and final follow up data by the end of third week. RESULTS: Results showed significant improvement in pain and disability (P≤0.05) in both groups. CONCLUSION It is concluded that both manual therapy and MTrPs therapy were equally effective in management of upper trapezius myofascial trigger points.